2011
DOI: 10.1158/0008-5472.can-10-3320
|View full text |Cite
|
Sign up to set email alerts
|

HIF Induces Human Embryonic Stem Cell Markers in Cancer Cells

Abstract: Low oxygen levels have shown to promote self-renewal in many stem cells. In tumors, hypoxia is associated with aggressive disease course and poor clinical outcomes. Furthermore, many aggressive tumors have shown to display gene expression signatures characteristic of human embryonic stem cells (hESC). We now tested whether hypoxia might be responsible for the hESC signature observed in aggressive tumors. We show that hypoxia, through hypoxia inducible factor (HIF), can induce a hESC-like transcriptional progra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
361
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 468 publications
(381 citation statements)
references
References 46 publications
15
361
1
4
Order By: Relevance
“…High NANOG mRNA (23) or protein (41) expression in primary human breast cancers is significantly associated with increased patient mortality. Other groups have implicated HIFs in the direct transcriptional activation of NANOG and other genes encoding pluripotency factors, both in human ESCs (42) and human cancer cells (17). We demonstrated that expression of ALKBH5 was necessary (Figs.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…High NANOG mRNA (23) or protein (41) expression in primary human breast cancers is significantly associated with increased patient mortality. Other groups have implicated HIFs in the direct transcriptional activation of NANOG and other genes encoding pluripotency factors, both in human ESCs (42) and human cancer cells (17). We demonstrated that expression of ALKBH5 was necessary (Figs.…”
Section: Discussionmentioning
confidence: 56%
“…In hypoxic breast cancer cells, HIFs activate the transcription of target genes that play important roles in tumor growth, angiogenesis, metabolic reprogramming, motility, invasion, metastasis, and resistance to chemotherapy (15,16). Recent studies have demonstrated that HIFs are required for the specification and/or maintenance of BCSCs in response to hypoxia (17)(18)(19)(20)(21) or chemotherapy (22,23), leading to direct or indirect transcriptional regulation of genes encoding the pluripotency factors NANOG, SOX2, and KLF4. In addition, HIF-1α is required for hypoxia-induced epithelial-mesenchymal transition (24), which is also linked to the BCSC phenotype (25).…”
mentioning
confidence: 99%
“…Recent studies, mostly via in vitro experimental manipulations ( Figure 5D), provide support to these possibilities. For example, culturing cancer cells under low O 2 tension increases the expression of 'stemness' genes and the percentage of phenotypic CSCs [127][128][129]. Experimental EMT and inflammatory cytokines IL-6, IL-8, TGFβ, and TNFα can all promote the manifestation of CSC phenotypes and properties [130][131][132][133][134][135].…”
Section: Intrinsic and Induced Plasticity In Csc Progenymentioning
confidence: 99%
“…Another study observed a somatic rare mutation at the same locus in 1/15 androgen-independent prostate tumours, whereas functional studies demonstrated in androgen-independent prostate cancer cells that the T-allele is associated with increased transcriptional activity and protein expression [28]. Therefore, we hypothesise that carrying the T-allele, which stabilises HIF1a protein and upregulates the HIF1A1 gene expression, may offer a selective advantage to androgen-independent tumour cells through the upregulation of several genes involved in metastasis, angiogenesis, epithelial-to-mesenchymal transition or in other cancer-associated mechanisms [10,23,[31][32][33]. The SNP in HIF1A at locus +1772 represents a germline variant, suggesting a cumulative impact of higher HIF1a expression since birth.…”
Section: Discussionmentioning
confidence: 99%